A Commentary qnd Analysis Of A Qudsiy (Holy) Hadith (O My servant, I have forbidden you oppression.) - Utkirkhon Mahmudov Fazliddinovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article analyzes one of the blessed Qudsi hadiths of Prophet Muhammad (peace be upon him). A Qudsi hadith is a narration that comes from Allah, but the words and phrases are conveyed by the Prophet (peace be upon him). The hadith presented in the article includes Allah's commands to His servants, His mercy, and His instructions for seeking guidance, forgiveness, sustenance, and protection from harm. The hadith emphasizes that all human beings are in constant need of Allah in both religious and worldly matters, and that only Allah can fulfill their needs. The importance of relying solely on Allah for all needs and the concept of personal accountability for one’s actions are also highlighted in the hadith.